Changing Agricultural Scenario and its Impact: a Study of Rural Punjab. - Sukhdev Singh and Maninder Kaur (2008)
The study reveals that materialism is on the rise in rural Punjab as most farmers have adopted new housing patterns coupled with all the facilities previously found in urban areas only. The availability of more durable goods with majority of the farmers indicates a clear shift towards material possession. Areas under wheat and paddy have shown a significant increase while other crops such as groundnut, sugarcane, gram and oilseeds have indicated a declining trend. Moreover, the timings for field visits have changed substantially. Modern machinery, automation in tube wells and the use of chemicals has reduced the longer working hours. Most farmers avail credit between Rs 1 lakh and Rs 2.5 lakh, which is taken from institutional and non-institutional sources, for purchase of farm inputs, repayment of old debts, and for expenditure on socio-religious ceremonies. Farmers purchase machinery not only for meeting their agriculture requirements but it is also seen as a prestige issue. Migratory labour is replacing local labour due to various reasons. The introduction of new technology and the use of agrochemicals have brought about changes in agriculture, and this in turn has affected the traditional social relationships. The Jajmani system is no longer prevalent in the countryside. Majority of the farmers prefer a nuclear family system, and have cited materialism and the urge to live independently as the main reasons for the change.